Data Warehouse Implementation For University Executive Information System with Speech Command Feature - Afandi, M. I.; E. D. Wahyuni (Future Science)
Higher education institutions have already started implementing Executive information System that consumed datawarehouse in order to support university executives to make better decision. Normally, the application are operated using mouse, keyboard, or touch-screen device which in some cases is not suitable for the users. The recent research and development in natural language processing opens up opportunity to be implemented in many information systems. This paper presents a prototype of executive information system with speech command feature which gives the users the comfort to request for information to be displayed on the screen using their voice.